2008
DOI: 10.1002/prot.21917
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a caesalpinoid (Chamaecrista fasciculata) hemoglobin: The structural transition from a nonsymbiotic hemoglobin to a leghemoglobin

Abstract: Nonsymbiotic hemoglobins (nsHbs) and leghemoglobins (Lbs) are plant proteins that can reversibly bind O(2) and other ligands. The nsHbs are hexacoordinate and appear to modulate cellular concentrations of NO and maintain energy levels under hypoxic conditions. The Lbs are pentacoordinate and facilitate the diffusion of O(2) to symbiotic bacteroids within legume root nodules. Multiple lines of evidence suggest that all plant Hbs evolved from a common ancestor and that Lbs originated from nsHbs. However, little … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Therefore, expression of Lb genes is also likely to be regulated by cytokinin, which plays important roles in RN symbiosis [100]. It is noteworthy that symbiotic Hbs in the actinorhiza plant Casuarina glauca and the caesalpinioid legume Chamaecrista fasciculata (which may have evolved nodulation independently from model papilionoid legumes) show functionally intermediate properties between Lbs and class-2 nsHbs [101,102], indicating Lbs evolved before legume diversification. The symbiotic Hb in non-legume Parasponia andersonii, which establishes RN symbiosis with Bradyrhizobium spp., has a root-nodule-specific promoter and has evolved from class-1 nsHbs [103,104], so that recruitment of nsHbs to symbiotic Hbs has occurred multiple times.…”
Section: Regulation Of Nitrogen Fixation In Host Plantsmentioning
confidence: 99%
“…Therefore, expression of Lb genes is also likely to be regulated by cytokinin, which plays important roles in RN symbiosis [100]. It is noteworthy that symbiotic Hbs in the actinorhiza plant Casuarina glauca and the caesalpinioid legume Chamaecrista fasciculata (which may have evolved nodulation independently from model papilionoid legumes) show functionally intermediate properties between Lbs and class-2 nsHbs [101,102], indicating Lbs evolved before legume diversification. The symbiotic Hb in non-legume Parasponia andersonii, which establishes RN symbiosis with Bradyrhizobium spp., has a root-nodule-specific promoter and has evolved from class-1 nsHbs [103,104], so that recruitment of nsHbs to symbiotic Hbs has occurred multiple times.…”
Section: Regulation Of Nitrogen Fixation In Host Plantsmentioning
confidence: 99%
“…Hirsch et al (2009) propose that Rhizobium infection threads in the nodule enter secondarily through crack entry since rhizobial infection threads abort in root hairs. Within nodules, a hemoglobin with reduced O 2 affinity has been characterized that is intermediate between nonsymbiotic hemoglobins and leghemoglobin, resembling a putative ancestral leghemoglobin (Gopalasubramaniam et al, 2008). Rhizobial strains selected for C. fasciulata were collected by the late Peter Graham and will become available from the U.S. Department of Agriculture Agricultural Research Service National Rhizobium Germplasm Resource Collection curated by Peter van Berkum.…”
Section: Nodulationmentioning
confidence: 99%
“…94 mya. Likewise, the structural analysis of primitive nsHbs and Lbs revealed that changes during the evolution of nsHbs to Lbs were a hexacoordinate to pentacoordinate transition at the heme prosthetic group, a length decrease at the CD-loop and N- and C-terminal regions, and a compaction of the protein into a globular structure 47 , 125 .…”
Section: Evolution Of Rice Hemoglobinsmentioning
confidence: 99%